Removal of Decaying DC Offset in Current Signals for Power System Phasor Estimation - Amir A. A., Eisa; K., Ramar (2008)
This paper presents a new method for the removal of decaying de offset from current signals in digital protective devices. The method is based on the fact that a purely sinusoidal signal has a zero average over a full cycle or multiples of the full cycle of its fundamental frequency, whereas an exponential signal has a nonzero average over that same interval. A fall cycle plus one sample of post fault data are required to calculate the parameters of the decaying dc offset in order to completely eliminate it from the current signal. Decaying dc offset removal is carried out before applying the current signal to the digital filter used for phasor estimation. The method has been tested by applying it to a fault current signal generated by computer simulation. Results obtained indicate that the method has greatly improved the performance of the full-cycle DFT algorithm. The new method can be applied in real time on digital protective devices because of its simplicity and computational efficiency.